2019
DOI: 10.1002/mc.22967
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling analysis upon acylcarnitines in tissues of hepatocellular carcinoma revealed the inhibited carnitine shuttle system caused by the downregulated carnitine palmitoyltransferase 2

Abstract: The carnitine shuttle system (CSS) plays a crucial role in the transportation of fatty acyls during fatty acid β‐oxidation for energy supplementation, especially in cases of high energy demand, such as in cancer. In this study, to systematically characterize alterations of the CSS in hepatocellular carcinoma (HCC), acylcarnitine metabolic profiling was carried out on 80 pairs of HCC tissues and adjacent noncancerous tissues (ANTs) by using ultra‐performance liquid chromatography coupled to mass spectrometry. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 55 publications
4
33
0
Order By: Relevance
“…Second, although carnitine homeostasis is maintained by dietary intake (mainly meat products) as well as endogenous synthesis and renal reabsorption 34 , we did not have data on dietary habits in this cohort. Third, although we and another group previously identified downregulation of CPT2 as a critical factor for acylcarnitine accumulation in HCC tissues 10,22 , the mechanism underlying the changes in serum acylcarnitine profiles during the progression of NAFLD remains unclear. One possibility is that FAO in patients with advanced-stage NASH may be impaired in the process of acyl-CoA dehydrogenation that is catalyzed by acyl-CoA dehydrogenases including very long-chain acyl-CoA dehydrogenase (VLCAD), long-chain acyl-CoA dehydrogenase (LCAD), and medium-chain acyl-CoA dehydrogenase (MCAD).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Second, although carnitine homeostasis is maintained by dietary intake (mainly meat products) as well as endogenous synthesis and renal reabsorption 34 , we did not have data on dietary habits in this cohort. Third, although we and another group previously identified downregulation of CPT2 as a critical factor for acylcarnitine accumulation in HCC tissues 10,22 , the mechanism underlying the changes in serum acylcarnitine profiles during the progression of NAFLD remains unclear. One possibility is that FAO in patients with advanced-stage NASH may be impaired in the process of acyl-CoA dehydrogenation that is catalyzed by acyl-CoA dehydrogenases including very long-chain acyl-CoA dehydrogenase (VLCAD), long-chain acyl-CoA dehydrogenase (LCAD), and medium-chain acyl-CoA dehydrogenase (MCAD).…”
Section: Discussionmentioning
confidence: 84%
“…Consistent with our results, Lu et al . recently reported that the serum and tissue levels of long-chain acylcarnitine species increased but those of short- and middle-chain acylcarnitine species decreased in patients with hepatitis virus-related HCC, and such changes in acylcarnitine profiles were caused by downregulation of CPT2 22 . In contrast, Zhou et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, acylcarnitines with medium-chain fatty acids can freely pass through the mitochondrial membranes and are utilized to produce fuel for energy [29,33]. Previous studies demonstrated that carnitine palmitoyltransferase 2 (CPT 2) expression is downregulated, thereby reducing hepatic beta-oxidation of fatty acids in patients with HCC [34,35]. A lack of CPT 2 expression ultimately leads to an increased level of long-chain acylcarnitines and reduced level of short- and medium-chain acylcarnitines in circulation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that carnitine palmitoyltransferase 2 (CPT 2) expression is downregulated, thereby reducing hepatic beta-oxidation of fatty acids in patients with HCC [34,35]. A lack of CPT 2 expression ultimately leads to an increased level of long-chain acylcarnitines and reduced level of short- and medium-chain acylcarnitines in circulation [34,35]. Therefore, we speculate that due to the rapid transport of medium-chain acylcarnitines into the liver, the cancer cells may utilize this energy source to proliferate.…”
Section: Discussionmentioning
confidence: 99%